DETECTION OF MRSA FROM NASAL CARRIER AMONG DIABETIC FOOT ULCER PATIENTS IN TERTIARY CARE HOSPITAL PUDUCHERRY - JAYARANI.K; SUNIL SHYAM SUNDARJI (International Journal of Pharma and Bio Sciences, 2015)
The purpose of this study was to evaluate risk factors for Methicillin-resistant Staphylococcus aureus (MRSA) from nasal carriers in patients hospitalized for diabetic foot ulcer infections. The study material consisted of nasal swabs collected from diabetic foot ulcer patients admitted at Sri Lakshmi Narayana Institute of medical sciences during the period of 3 months from November 2014 to January 2015. All the samples were subjected to gram staining and bacterial culture and S. aureus isolates were screened for MRSA prevalence using microbiological methods. All the clinical isolates are subjected to antimicrobial susceptibility testing on Mueller Hinton agar using the Kirby-Bauer disc diffusion method. S. aureus was the most common pathogen among the Gram-positive bacteria isolated from nasal carriers of diabetic foot ulcer patients. Out of 100samples, 65 Staphylococcus aureus was isolated, 40 (40%) were found to be Methicillin-resistant Staphylococcus aureus (MRSA) (MRSA) and 25 (25%) were found to be Methicillin sensitive Staphylococcus aureus (MSSA).Patients with diabetes with high blood sugar level (350-450mg/dl) were predominantly affected and the foot ulcers were significantly higher in males (70%). Identifying risk factors for MRSA infections could improve prevention and treatment in diabetic foot infections, reduce resistance patterns and reduce health care costs.